P45 Co-morbidities in Alpha-1-antitrypsin deficiency. (2nd December 2011) - Stone, H; Pye, A; Stockley, R A
Abstract : Introduction: Chronic obstructive pulmonary disease is well recognised to be a multi system inflammatory condition with systemic manifestations, including co morbidities such as diabetes, ischaemic heart disease and osteoporosis. Patients with alpha-1 antitrypsin deficiency (A1ATD) have a similar spectrum of lung disease and increased levels inflammation and recognised associations with vasculitis and panniculitis. Our aim was to characterise the co morbidities of the UK cohort of patients with A1ATD. Methods: A retrospective review of the notes of patients with the ZZ phenotype was undertaken for patients who attended the Alpha-1-Antitrypsin Deficiency Assessment and Programme for Treatment (ADAPT) Project in Birmingham, between the years 2001 and 2011. Results: 764 sets of notes were reviewed. Of the patients included, 75 had died. The most common known co morbidity encountered was hypertension (94 patients, 12.3%), followed by depression (34 patients 4.5%) and osteoporosis (40 patients 5.2%). Interestingly, 10 patients in the cohort had been diagnosed with ulcerative colitis (UC), 4 had proven factor V Leiden deficiency and 25 were hypothyroid. Conclusion: Depression and osteoporosis are recognised co morbidities in usual COPD, and are among the most common findings in the A1ATD patients, together with hypertension. The figures are lower than reported in usual COPD. There were more patients than expected who had Factor V Leiden deficiency (56 in 12 000 vs 10 in 12 000 of the UK adult population) and 11 potential patients on long-term anticoagulation in whom it was no longer possible to measure factor V Leiden. UC has a prevalence of 3–9 cases per 10 000 in the UK but our figures suggest 130 per 10 000. Finally, thyroid disease is usually more common in women, affecting 15 in 1000 in the UK. In our patient group, the incidence is double (32 in 1000). Overall, the incidence of several inflammatory/autoimmune diseases was higher than predicted for the UK population and a potential link to a coagulopathy was identified.